Implementasi Program Pelatihan Kerja dengan Dana Bagi Hasil Cukai Hasil Tembakau dalam Mengatasi Tingkat Pengangguran di Kabupaten Nganjuk - Febriana, Ega Jelita; Muljanto, Muhammad Agus (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to evaluate the implementation of the job training program funded by the Tobacco Excise Revenue Sharing Fund (DBHCHT) in reducing the unemployment rate in Nganjuk Regency. DBHCHT is a funding source derived from tobacco excise revenue, allocated to various development sectors in the regions, including the labor sector. Nganjuk Regency, as a DBHCHT beneficiary, has implemented several job training programs to enhance community skills, particularly for groups affected by tobacco excise regulations and those categorized as open unemployment. The method used in this research is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with representatives from the Department of Manpower, program trainers, and training participants, as well as field observations and related document analysis. The results of the study indicate that the DBHCHT job training program in Nganjuk Regency has had a positive impact on improving participants' work skills and readiness to enter the workforce. However, the implementation of this program still faces various challenges, including limited participant capacity, a mismatch between the training provided and the needs of the local job market, and the absence of an effective mentoring and job placement mechanism. Therefore, synergy between various sectors, more accurate identification of labor market needs, and the implementation of a continuous monitoring and evaluation system are required. These steps are expected to optimize the implementation of the DBHCHT job training program so that it can significantly contribute to reducing the unemployment rate in Nganjuk Regency.